The Urgency of Developing Students' Critical Thinking Skills in Class XI Fiqh Learning - Desinta M. Mahmud; Rahmawati; Ruwiah A. Buhungo; Ni’ma M. Alhabsyi (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the urgency of developing students’ critical thinking skills in Grade XI Fiqh learning at Madrasah Aliyah Negeri 1 Kabupaten Gorontalo and to analyze teachers’ efforts and their impact on students’ abilities. This research employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation involving the madrasah principal, Fiqh teacher, and Grade XI students as informants. Data analysis was conducted through data collection, data condensation, data display, and conclusion drawing, while data validity was ensured through source, technique, and time triangulation. The findings reveal that developing critical thinking skills in Fiqh learning is highly important because it helps students understand Islamic law more deeply, not merely memorize learning materials, but also analyze, evaluate, and solve religious problems contextually. Teachers’ efforts were implemented through discussion, question-and-answer sessions, case studies, and problem-solving activities. These strategies positively influenced students’ learning participation, confidence in expressing opinions, argumentative ability, and ability to connect Fiqh materials with everyday life. The challenges identified include differences in students’ abilities, lack of self-confidence, passivity among some students, and limited instructional time.